Is A+B invertible?

Algebra Level 2

Let A A and B B be two n × n n\times n matrices that commute and such that for some positive integers p p and q q , A p = I n A^p=I_n and B q = O n B^q=O_n . Is A + B A+B invertible? If so, find its inverse.

Yes No

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Patrick Corn
Jun 12, 2020

Clearly A A is invertible (indeed, det ( A ) p = det ( A p ) = det ( I ) = 1 , \det(A)^p = \det(A^p) = \det(I) = 1, so det ( A ) 0 \det(A) \ne 0 ). Find k k such that 2 k q . 2^k \ge q. Then ( A + B ) ( A B ) ( A 2 + B 2 ) ( A 4 + B 4 ) ( ) ( A 2 k 1 + B 2 k 1 ) ( A 1 ) 2 k = ( A 2 k B 2 k ) ( A 1 ) 2 k = A 2 k ( A 1 ) 2 k = I . (A+B)(A-B)(A^2+B^2)(A^4+B^4)(\cdots)(A^{2^{k-1}} + B^{2^{k-1}})(A^{-1})^{2^k} = (A^{2^k} - B^{2^k})(A^{-1})^{2^k} = A^{2^k} (A^{-1})^{2^k} = I.

That's a great solution!

Chris Lewis - 1 year ago
Nick Kent
Jun 12, 2020

Let's note that A p 1 {A}^{p-1} is the inverse of A A .

Assume there is an inverse, then M = ( A + B ) 1 M = {(A+B)}^{-1} :

  • M ( A + B ) = I n M(A+B) = {I}_{n}
  • M A + M B = I n MA + MB = {I}_{n}
  • M A B q 1 + M B q = B q 1 MA{B}^{q-1} + M{B}^{q} = {B}^{q-1}
  • M A B q 1 + O n = B q 1 MA{B}^{q-1} + {O}_{n} = {B}^{q-1}
  • M A B q 1 = B q 1 MA{B}^{q-1} = {B}^{q-1}

This holds true if M A = I n MA = {I}_{n} . Then M = A p 1 M = {A}^{p-1} :

  • A p 1 ( A + B ) = I n {A}^{p-1}(A+B) = {I}_{n}
  • A p + A p 1 B = A p {A}^{p} + {A}^{p-1}B = {A}^{p}
  • A p 1 B = O n {A}^{p-1}B = {O}_{n}
  • A p B = O n {A}^{p}B = {O}_{n}
  • B = O n B = {O}_{n}

That's all i got, obviously not enough so feel free to add on missing parts)

Théo Leblanc
Jun 12, 2020

Because A A and B B commute we heve the usual identity : a n b n = ( a b ) ( a n 1 + a n 2 b + + a b n 2 + b n 1 ) a^n-b^n=(a-b)(a^{n-1} + a^{n-2}b + \cdots + ab^{n-2} + b^{n-1})

Apply it to a = A a=A and b = B b=-B , note that ( B ) p = ( 1 ) p B p = 0 (-B)^p=(-1)^p B^p = 0

I n = A p ( B ) p = ( A + B ) ( A p 1 + A p 2 ( B ) + + A ( B ) p 2 + ( B ) p 1 ) I_n = A^p - (-B)^p = (A+B)(A^{p-1} + A^{p-2}(-B)+ \cdots + A(-B)^{p-2} + (-B)^{p-1})

we have found the inverse of A + B A+B .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...